Measuring Language Gains in a Foreign Language Context - Muñoz Restrepo, Ana; Valderrama Carvajal, Isabel; Lopez Muñoz, Alejandra; Avendaño Franco, Ricardo (Colombian Applied Linguistics Journal, 2020)
Learning gain can be defined as the difference between students’ language competences demonstrated at two different points in time. In this article, we reported on a small-scale study aimed at measuring learning gains and piloting the methods chosen. Fourteen students of English as a foreign language participated in the study. We employed a student self-report survey, an oral performance assessment task and a standardised test for data gathering, and we applied them at three different moments during the eight-month study. Our data analysis includes the comparison of percentages rendered by test scores, the estimation of means for oral task scores and grouping and coding for qualitative data in the survey. Results show the gradual pattern of language improvement and the suitability of methods. These results can help stakeholders or policymakers in selecting relevant evidence to improve accountability in decision-making. We have provided conclusions and recommendations below for a larger scale study.